Exploring Organisational Change using Corporate Non-Financial Disclosure - Euler, Anne (2006)
Today, most companies are faced with an increasing pressure to engage in actions to meet rapidly changing expectations about their social responsibilities and to 'account for' their social and ethical performance. This has led to an ever increasing number of companies which produce non-financial reports. The central question of this study is whether actual organisational change is taking place in the face of the shifting demands or if companies are only improving their non-financial disclosure in order to enforce the 'status quo'. This study firstly examines the literature related to non-financial reporting and the existing standards and external benchmarks. It also discusses the role of non-financial disclosure. Then, the relationship of non-financial disclosure and organisational change is illustrated and an organisational change framework presented. Afterwards, this paper evaluates six companies' non-financial disclosure using the Accountability Rating and Laughlin's typology of organisational change. The main finding of this study is that none of the companies is undergoing fundamental deep-seated change that manifests itself in all aspects of the business. However, some are prepared better than others and might be able to develop a sustainable business model in the near future. Nevertheless, it is crucial that corporate leaders support these changes.